KESENYAPAN NARASI KOLONIALISME DALAM NOVEL-NOVEL SUNDA RENTANG 1914—1940: WACANA MENGINGAT DAN MELUPAKAN (The Silent of Colonialism Narratives in Sundanese Novels Circa 1914—1940: Memory Discourse about Remembering and Forgetting) - Hudayat, Asep Yusup; Rahayu, Lina Meilinawati; Muhtadin, Teddi A.N. (Kantor Bahasa Provinsi Sulawesi Tenggara, 2023)
In the early 20th century circa 1914–1940 were Sundanese novels almost